Analysing the quality of service and designing the appropriate marketing mix for Nottingham Counselling Service’s (NCS) offering to the GP Market - Muppala Venkata, Kalyan Kumar (2011)
This study aims to contribute to the existing literature of services marketing. The purpose of this dissertation is to understand the factors influencing the GP’s referral decisions to counselling services in order to market the existing services of NCS to the GP market and to the Consortia.